Online Meal Delivery In Indonesia: Factors Impacting Consumer Persuasion - Widarto Rachbini; Tiolina Evi; Harimurti Wulandjani; Suyanto; Emi Rahmawati (Jurnal Manajemen, 2024)
This study empirically examines the impact of price-savings orientation on utilitarian and hedonic app browsing, as well as the influence of utilitarian app browsing, hedonic app browsing, and social influence on consumer persuasion within the Indonesian online meal delivery app context. Primary data was collected through online questionnaires distributed via Google Forms, utilising purposive sampling criteria explicitly targeting users who had conducted transactions on these platforms. The analysis employed the Structural Equation Model (SEM) with Smart PLS software, revealing significant findings. Price-savings orientation positively affected utilitarian and hedonic app browsing, while utilitarian app browsing and social influence significantly influenced consumer persuasion. Implications suggest that future online meal delivery platform development and marketing should prioritise pricing and social influence. Subsequent research should extend this framework to other digital-based business sectors, focusing on a more diverse range of productive-age respondents.